Globalization and some of its impact on education and culture - Abdul Razak, Mohd Abbas (2011)
In the history of Islam, the fall of Baghdad in 1258 indicates the decline of the Islamic empires. The fall of the empires also marked the fall of the Islamic civilization and intellectualism. As the Islamic empires fell one after another, starting with Baghdad, this left the Muslims in a pathetic condition, hardly able to regain the prestigious position once they held on the world stage. The internal conflicts within the Ummah, also in a way failed them in making any significant contribution during the great Industrial Revolution that happened in the West. After that, Western colonization of Muslim lands, to some extent deprived them the success of reconstructing and regaining the great civilization once they had during their heydays. Evers since the fall of Baghdad, the Muslims are constantly bombarded with challenges they have to face in maintaining their faith, culture and heritage. In modern times, after their independence, one of the serious problems they have to face is globalization. Globalization which started some time ago is an ongoing thing that cannot be stopped. It is a multi-faceted phenomenon which ramifies into all areas of the human life. Since the idea of globalization is a thing that comes from the rich and affluent countries of the West, many in the developing and third world countries welcome it with much delight as it offers them a great deal in terms of capital flow which promises prosperity. Others perceive it with a doubtful and skeptical attitude by questioning as to what are the hidden agendas of globalization. To them, globalization is a new agenda of the West to re-colonize the East. It is seen as a new approach of how the Western hegemony can be imposed on the political, economic, social, cultural and other aspects of the people in the East, particularly in the Muslim world. In the light of the present world scenario, this paper intends to explore what globalization is all about, what sort of impact it has on the Islamic civilization, very particularly in the areas of education and culture. Since globalization is irreversible, the paper also aims at discussing on how the Muslim countries should strategize in facing the ferocious onslaught of the tidal waves of globalization that have touched their shores. Keywords: Globalization, Impact, Education, Culture & Re-colonization